2023
DOI: 10.18632/aging.205214
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis of the oncogenic role of optic atrophy 1 in human cancer

Ziyi Wu,
Nuo Xu,
Guoqing Li
et al.

Abstract: Objective: To investigate the prognostic significance of optic atrophy 1 ( OPA1 ) in pan-cancer and analyze the relationship between OPA1 and immune infiltration in cancer. Results: OPA1 exhibited high expression levels or mutations in various types of tumor cells, and its expression levels were significantly correlated with the survival rate of tumor patients. In different tumor tissues, there was a notable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Studies have indicated that OPA1 is overexpressed or mutated across various cancers and is closely associated with protein phosphorylation, patient prognosis, and immune cell infiltration 24 . Additionally, research has shown concurrent amplification of OPA1 and MFN1 copy numbers, synergistically activated in tumor epithelial cells in lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that OPA1 is overexpressed or mutated across various cancers and is closely associated with protein phosphorylation, patient prognosis, and immune cell infiltration 24 . Additionally, research has shown concurrent amplification of OPA1 and MFN1 copy numbers, synergistically activated in tumor epithelial cells in lung cancer tissues.…”
Section: Discussionmentioning
confidence: 99%